2023
DOI: 10.5772/intechopen.108809
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Conservation of Mountain Ungulate in the Western and Trans-Himalayas, India

Abstract: The Western and Trans-Himalayan region of India is home to several unique and threatened mountain ungulates including Kashmir red deer or Hangul, Kashmir Musk deer, Urial, Argali, Tibetan Antelope or Chiru, Tibetan Gazelle, Wild Yak, and Wild Ass that are endemic to this region. However, this ecologically significant and diverse biodiversity is threatened by climate change, habitat degradation, and fragmentation accompanied by overexploitation in the form of poaching. In locations where the ungulates are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the other hand, overexploitation in the form of illicit wildlife poaching, habitat degradation, and fragmentation pose serious threats to its main abode, the Greater Dachigam landscape. These issues have led to ecological isolation, population decline, and inbreeding and brought the species to the brink (Ahmad, 2022;Ahmad et al, 2023). Although the establishment of protected areas is a helpful conservation strategy, it has been found that poor management and smaller size may negate the advantages of all conservation initiatives aimed at enhancing biodiversity.…”
Section: Implications For Conservation Of Dachigam Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, overexploitation in the form of illicit wildlife poaching, habitat degradation, and fragmentation pose serious threats to its main abode, the Greater Dachigam landscape. These issues have led to ecological isolation, population decline, and inbreeding and brought the species to the brink (Ahmad, 2022;Ahmad et al, 2023). Although the establishment of protected areas is a helpful conservation strategy, it has been found that poor management and smaller size may negate the advantages of all conservation initiatives aimed at enhancing biodiversity.…”
Section: Implications For Conservation Of Dachigam Landscapementioning
confidence: 99%
“…Many studies have assumed that the Dachigam landscape is critical for Hangul foraging habitats and provides key habitats (Ahmad 2004; Sharma et al 2010; Mukherjee et al 2021). The population of Hangul has drastically dropped due to habitat loss, overgrazing, poaching, and disturbances caused by human activities (Shah et al 2011; Hassan et al 2013;Ahmad 2022). Furthermore, Hangul migrates to alpine pastures in summer, which have been disturbed due to heavy livestock grazing and turmoil for the last few decades, resulting in a negative impact on the Hangul's population and distribution (Kaul et al 2020;Bhat et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Blue sheep has been listed as the Least concern while Ladakh urial and Himalayan ibex are listed as Near-threatened (IUCN 2023). Blue sheep is distributed across the Tibetan plateau and its surrounding mountain ranges, while Himalayan ibex is distributed in the mountains of Pakistan, China, India, Afghanistan, Kyrgyzstan, Kazakhstan, Uzbekistan, Mongolia, Russia, and Tajikistan (Khattak et al 2020;Ahmad 2022). Ladakh urial, a subspecies of urial is restricted to the bank of river Indus, Shayok and its major tributaries in Ladakh, India and Gilgit-Baltistan, Pakistan (Khara et al 2021).…”
Section: Introductionmentioning
confidence: 99%